Sister Stella L. - De Leon, Mike. ([Quezon City] Regal Films, 1984)
Story of an activist accused of subversion for her involvement in a strike. Her ex-boyfriend journalist?s pro-labor articles are suppressed, strikers are brutally beaten, tortured and salvaged," but Sister Stella L. urges them on with a closing speech full of leftist slogans.
Vilma Santos, Jay Ilagan, Gina Alajar, Laurice Guillen.
DVD
In Tagalog.
Keywords: Nuns -- Philippines -- Drama; Strikes and lockouts -- Philippines -- Drama; Labor unions -- Philippines -- Drama; Feature films -- Philippines